Structure Realization and Motion Control of a Manipulator for the Production and Assembling of the Fragile Pyrophyllite Block - Liangwen Wang; Jihao Zhang; Yalin Mu; Qinghua Zhang; Ruolan Wang; Shizhao Zhang (Jixie chuandong)
According to the production process requirements of the pyrophyllite block，which is raw material for synthetic diamond，a manipulator with internal bracing grasping and pressing assembly for fragile cylindrical inner wall parts is designed. The manipulator completes the grasping and assembling together，and the structure of the pressing action is designed as a barrel-shaped palm，and the three circular arc fingers with internal bracing grasping，which complete the grasping and transferring action，are nested in the inner cylindrical surface of the barrel-shaped palm. Based on the introduction of the overall structure of the manipulator，the selections of the pushing cylinder and the pneumatic control system are discussed. The influence of different motion laws on the stability of the operation process is investigated when controlling the transfer operation of the manipulator. The theoretical analysis of the motion laws and the Adams motion simulation of the manipulator working process indicate that better motion performance can be obtained by using modified trapezoidal motion laws to control the transferring motion of the manipulator. The results of the study laid a good foundation for the operation of the improved manipulator system.